2016
DOI: 10.4491/eer.2016.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of kinetics behavior of electrocoagulation process for the removal of suspended solids and metals from synthetic water

Abstract: Globalization, industrialization, mining, and uncontrolled population growth have fostered a shortage of potable water. Therefore, it has become imperative to understand an effective and reasonable water purification technique. A renewed interest in electrocoagulation (EC) has been spurred by the search for reliable, cost-effective, water-treatment processes. This paper has elucidated a technical approach for getting rid of heavy metals and total suspended solids (TSS) from synthetic water using an aluminum el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Since the Cu layers are deposited on Al substrates, electrocoagulation process may occur during the reaction due to the anodic reaction at Al surface. The anodically generated Al 3+ ions support the electrocoagulation [24,25]. In literature, it has been reported that electrocoagulation process does support the nitrate removal [26].…”
Section: Cathode Materials Developmentmentioning
confidence: 94%
“…Since the Cu layers are deposited on Al substrates, electrocoagulation process may occur during the reaction due to the anodic reaction at Al surface. The anodically generated Al 3+ ions support the electrocoagulation [24,25]. In literature, it has been reported that electrocoagulation process does support the nitrate removal [26].…”
Section: Cathode Materials Developmentmentioning
confidence: 94%
“…The largest % of total solid suspended removal (40%) occurred at pHi 3. In this research, suspended solid removal is lower than suspended removal (76.6%) from synthetic water using an aluminum electrode [19]. the first 5 minutes Ni removal reached 100% at pHi 5 and 9, 80% at pHi 7.5, and <20% at pHi 3.…”
Section: Advances In Engineeringmentioning
confidence: 63%
“…Moreover, pH between 5 to 6, the Al(OH) 2+ and Al(OH) 2 + was predominant; pH>9, the Al(OH) 4 was predominant [44]. The Al(OH) 3 having a large surface area helpful to trap the colloidal particles and adsorb the soluble compounds, results, the peak removal efficiency was happen [72,92]. The different metals were influenced in the EC process.…”
Section: Influence Of Phmentioning
confidence: 99%